2021
DOI: 10.3389/fmars.2020.625766
|View full text |Cite
|
Sign up to set email alerts
|

Shining Light on Data-Poor Coastal Fisheries

Abstract: Coastal fisheries provide livelihoods and sustenance for millions of people globally but are often poorly documented. Data scarcity, particularly relating to spatio-temporal trends in catch and effort, compounds wider issues of governance capacity. This can hinder the implementation and effectiveness of spatial tools for fisheries management or conservation. This issue is acute in developing and low-income regions with many small-scale inshore fisheries and high marine biodiversity, such as Southeast Asia. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…activities, biodiversity and socioeconomic needs; detailed consultations with the fishing dependent communities and management planning in which the communities proposed their own no-take zones, seasonally closed areas, gear-restricted zones and protected turtle nesting beaches (Exeter et al, 2021;WCS, 2018). Following this process, the area was officially accepted by the government in 2018 as Myanmar's first marine fisheries comanagement area (Latt, 2019).…”
Section: Kyeintali Marine Fisheries Co-management Areamentioning
confidence: 99%
“…activities, biodiversity and socioeconomic needs; detailed consultations with the fishing dependent communities and management planning in which the communities proposed their own no-take zones, seasonally closed areas, gear-restricted zones and protected turtle nesting beaches (Exeter et al, 2021;WCS, 2018). Following this process, the area was officially accepted by the government in 2018 as Myanmar's first marine fisheries comanagement area (Latt, 2019).…”
Section: Kyeintali Marine Fisheries Co-management Areamentioning
confidence: 99%
“…Additional vessel tracking methods are important to capture fishing activity that is missed by AIS (see review by Iacarella et al, 2021). In particular, the utility of AIS for monitoring CAs is more limited for countries that do not mandate carriage by fishing or small vessels (Exeter et al, 2021; Kanjir et al, 2018), as well as in cases of illegal fishing where AIS message transmission may be blocked or falsified (Ford et al, 2018; Rowlands et al, 2019). A complementary approach to the AIS‐based method is the use of information collected on vessels by aerial surveillance (hereafter, “flyover”) programs.…”
Section: Introductionmentioning
confidence: 99%
“…to conduct an in-depth study on illegal fishing in sensitive areas between North Korea, Japan, and Russia [33]. Exeter et al utilizes VIIRS boat detections (VBD) and GPS data to predict fishing effort, biomass and value, as well as the spatial and temporal distribution of catch [34].…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the existing studies have focused more on the analysis and mining of the fishing intensity characteristics of Marine fisheries by using a single data source [13,25]. Although there are cases in existing studies that have combined multiple sources of data, most of them have focused on illegal fishing at sea, and there are still no cases that combine the advantages of the two and explore fishing intensity information of Marine fisheries through their fusion [29][30][31][32]34].…”
Section: Introductionmentioning
confidence: 99%